Praktik Kewirausahaan Sosial Berbasis Pembangkit Listrik Mikrohidro di Perdesaan Jawa Barat (Studi Kasus Desa Cintamekar, Kabupaten Subang) - Kuntari, Wien; Sarwoprasodjo, Sarwititi; Nurmalina, Rita; Sarma, Ma’mun (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2023)
Cintamekar Village in Subang Regency, West Java, is a peripheral village. One of its characteristics is that residents, especially from the pre-prosperous group, have not been able to enjoy the flow of electricity even though the source of electricity through the PLN is available. To overcome this, on the initiative of the non-governmental organization Initiative of People's Business and Economy (IBEKA), a PLTMH was built in the area. The purpose of this research is to analyze factors affecting social entrepreneurship for community empowerment. The research uses a quantitative approach which is reinforced by qualitative data. The method chosen is the case study. The results showed that overall, the formation of cooperatives was able to build social entrepreneurship by creating social benefits (score 3.6), carrying out social innovation (score above 3), and making the economic activities of citizens more diverse (score 4). The results from the data processed using SEM-PLS show that the development of social entrepreneurship is influenced by the characteristics of technology and innovation by 0.281. The communication channel factor is more dominant in influencing the development of social entrepreneurship, which is equal to 0.487. These two factors explained that there was a change of 33.3 percent in social entrepreneurship. The social entrepreneurship practice of the PLTMH program in Cintamekar Village is built on the characteristics of technology, innovation, and communication channels. The characteristics of technology and innovation as well as communication channels are the driving force for residents to change their social entrepreneurship behavior. This means that the technological and innovation characteristics of the PLTMH development and the communication channels used, through cooperative institutions, have a good impact on the development of social entrepreneurship in Cintamekar Village, and as a whole, they are able to build social entrepreneurship in creating social innovation and economic activities.